Analisis Peresepan Obat yang Berpotensi Tidak Tepat Berdasarkan Kriteria STOPP Pada Pasien Geriatri - Salsabilla, Riefa Ayu; Pardilawati, Citra Yuliyanda; Iqbal, Muhammad; Oktarlina, Rasmi Zakiah (CV. Jasa Sukses Abadi, 2024)
Potentially inappropriate prescribing (PIP) is a drug prescription without a proper clinical indication. The tools used to identify PIP in the geriatric patient is the STOPP criteria. The STOPP criteria evidently to improve treatment suitability, reduce medical costs, and reduce the occurrence of adverse drug reaction. The aim of this study is to evaluate the potentially inappropriate prescribing in geriatric patients using the STOPP criteria. This study is observational study used a cross-sectional approach. Geriatrics is an age group that is vulnerable to the side effects of drug use. Drug administration in geriatric patients is complex and requires a lot of consideration due changes in body composition and function, comorbidities, sensory and cognitive disorders, and polypharmacy, so that assistance with Potentially Inappropriate Medications (PIMs) and PPOs (Potentially Prescription Omissions) is important to improve the quality of treatment.